Anatomy : a love story - Schwartz, Dana (Wednesday Books, 2022)
Hazel Sinnett is a medical student in 19th century Scotland who, after being kicked out because of her gender, works with new attractive acquaintance Jack Currer to procure dead bodies to study, but they soon discover secrets buried in the heart of Edinburgh society.